Value and discriminative power of the seven‐item eustachian tube dysfunction questionnaire. (17th April 2015) - Van Roeyen, Shari; Van de Heyning, Paul; Van Rompaey, Vincent
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Obstructive eustachian tube (ET) dysfunction is a common condition associated with various otologic symptoms. The current lack of a diagnostic gold standard makes diagnosis and evaluation at follow‐up difficult. The aim of the study was to determine the value and discriminative power of the seven‐item Eustachian Tube Dysfunction Questionnaire (ETDQ‐7) in patients with obstructive ET dysfunction and patulous ET. Study design Diagnostic test study. Methods The ETDQ‐7 was completed by 39 patients with obstructive ET dysfunction, eight patients with patulous ET, and 22 healthy controls. The internal consistency was evaluated using the Cronbach α coefficient. Receiver operating characteristic (ROC) was determined as an accuracy measure. Results The mean ETDQ‐7 total score was 9.91 in the control group, 25.77 in the patients with obstructive ET dysfunction, and 27 in the patulous ET group. The Cronbach α coefficient was 0.795 in the obstructive ET group and 0.72 in the patulous ET group, demonstrating adequate reliability. The area under the curve in ROC analysis for the obstructive ET group was 95% and 96% for the patulous ET dysfunction group, which confirms its excellent discriminant validity toward the healthy control group. However, the ETDQ‐7 cannot discriminate between obstructive ET dysfunction and patulous ET. Conclusions The ETDQ‐7 can be a useful disease‐specific rating scale for ET dysfunction but is unable to discriminate between patients with obstructive ET dysfunction and patulous ET. Level of Evidence 3b Laryngoscope, 125:2553–2556, 2015